Pyrolytic Conversion of Palm Kernel Shells To Biochar and Comparative Insights with Incineration and Gasification for Environmental Sustainability - Dewi, Shafira Quamila; Dahlan, Astryd Viandila; Hartono, Djoko M. (Indonesian Journal of Multidisciplinary Science, 2025)
The palm oil industry produces large volumes of palm kernel shell (PKS) solid waste, most of which has been utilized as biomass, but some of which has the potential to increase greenhouse gas emissions if not managed optimally. Pyrolysis of PKS to biochar offers a sustainable solution to reduce environmental impacts while producing value-added products. This study aims to compare various pyrolysis methods and operational conditions used in the conversion of PKS and other palm oil wastes, and to identify the main results, applications, and environmental benefits of each approach. The findings of this study are that the optimal conditions for biochar production are slow pyrolysis (400–600°C, 30–90 minutes residence time) with a yield of 33–52%. Biochar can be applied in Soil Improvement and Agriculture Increasing soil fertility and carbon sequestration (CSP 0.63 kgCO?/kg PKS), Air Treatment and Pollutant Adsorption, Energy and Fuel (made into briquettes), Health and Safety (Reducing environmental toxicity), Industrial and Material Applications (Raw material for activated carbon production). Comparing to inceneration and gasification, pyrolysis of PKS offers superior environmental sustainability when biochar is sequestered or utilized in high-value applications. Its dual benefits of renewable energy recovery and carbon storage address both immediate energy needs and long-term climate change mitigation.